Drivers of Clan Conflicts: A Perspective of the Role of Al-Shabaab in Garissa County, Kenya - Stephen, K. Rotich; Warfa, O. Ahmed (Budapest International Research and Critics University, 2020)
The purpose of the study was to investigate the relationship between the drivers of intra-clan-based conflicts and the involvement of external actors that has remained indefinable in Garissa County. The three sub-counties: Garissa Township, Ijara and Fafi were purposively selected for the study because of prolonged and unresolved intra-clan conflicts coupled with militia group of Al-Shabaab attacks over the past years. Qualitative approach was used to seek understanding of drivers of intra-clan conflicts and involvement of violent extremism. The study involves primarily 35 Key Informants drawn from security agencies, Clan elders, Religious leaders and Civil societies across the three sub-counties. The study established that competition over natural resources: water; pasture and land are the main causes of intra-clan conflicts. The respondents attest that intra-clan conflicts have been accelerated by clan identity politics, poverty, illiteracy, unemployment and Al-Shabaab infiltration. The devolution has elevated competition for political leadership due to sharing of county resources and employment along the sub-clans. The study found some respondents attributing Kenya’s military operation in Somalia to reciprocal attacks by Al-Shabaab in the county. The research established that over the years, Somali clan conflicts and hostility have spilled over into North Eastern Kenya, creating security threat and undermining community peace and cohesion. The porous border of Kenya-Somali has made it easy for some sub-clans to communicate with their kinsmen’s counterparts and obtain guns that are readily available in Somalia. The perception of injustices and sense of marginalization amongst the Muslims have provided fertile ground for Al-Shabaab which has diverted attention of security agencies to violent extremism rather than clan conflicts. The study recommends enhancement of inclusive peace committee and collaboration of community with administration and security agencies to tie together peace. There is also a need for openness of politicians to advocate for impartiality, clan conflicts resolution and countering violent extremism through policy framework in the county assembly.